Weak asymmetric interspecific aggression and divergent habitat preferences at an elevational contact zone between tropical songbirds. (26th November 2019) - Jones, Samuel E. I.; Tobias, Joseph A.; Freeman, Robin; Portugal, Steven J.
Abstract : Closely related tropical bird species often occupy mutually exclusive elevational ranges, but the mechanisms generating and maintaining this pattern remain poorly understood. One hypothesis is that replacement species are segregated by interference competition (e.g. territorial aggression), but the extent to which competition combines with other key factors such as specialization to distinct habitats remains little studied. Using vegetation surveys and reciprocal playback experiments, we explored the dynamics of interspecific aggression between two Nightingale‐Thrushes Catharus sp. in Central America. We show that lower‐elevation Black‐headed Nightingale‐Thrushes Catharus mexicanus are aggressive towards higher‐elevation Ruddy‐capped Nightingale‐Thrushes Catharus frantzii where they meet at contact zones. However, interspecific aggressive responses were weak and unidirectional, and the two species were associated with different habitats. We conclude that the contact zone is maintained and located primarily by habitat selection, and is probably reinforced by interspecific aggression. This has important implications for understanding how montane species will respond to climate change because the pace and extent of range shifts will not depend solely on habitat shifts or interspecific competition, but instead on interactions between these two factors.